The Pengaruh Penerapan Model Pembelajaran Index Card Match terhadap Hasil Belajar Siswa dalam Pembelajaran Geografi di SMA Laboratorium Undiksha - Piscesita, Brilliantari Boeky; Astawa, Ida Bagus Made; Wesnawa, I Gede Astra (Jurnal Pendidikan Geografi Undiksha, 2025)
The designs of our  research are to analyze the utilization of the Index Card Match learning model in high school geography learning, analyze student learning outcomes before and after the application of the Index Card Match learning model in geography learning in high school, analyze the effect of the Index learning model Card Match in geography learning on student learning outcomes in high school, and highlights the obstacles faced by teachers in implementing the Index Card Match learning model in geography learning in high school. This study used an experiment with the Non-equivalent Control Group Design with the observation and tests Method. The outcomes declared that The Index Card Match Learning Model in geography learning at SMAS Laboratory Undiksha can apply teachers in the "very good" category and achieve a score of 88.5. Student Learning Outcomes have increased after the implementation of the Index Card Match Learning Model of 55,40%. The Index Card Match Learning Model has a significant effect on Student Geography Learning Outcomes with a significance of 0.000 <0.050. Moreover, tThere are no problems, either from the teacher or from the students therefore the Index Card Match learning model can also be applied to other learning materials besides atmosphere.